SELF-MONITORING IS NOT JUST FOR A STUDY, SELF-MONITORING IS FOR LIFE: ANALYSIS OF PATIENT LIKELIHOOD TO CONTINUE SELF-MONITORING FOLLOWING A HYPERTENSION SELF-MANAGEMENT STUDY. (June 2018) - Schwartz, C.; Koshiaris, C.; Bray, E.; Greenfield, S.; Haque, M.; Hobbs, R.; Little, P.; Mant, J.; Williams, B.; McManus, R.
Abstract : Objective: Self-management in the TASMIN-SR trial successfully reduced and controlled blood pressure (BP) compared to clinic monitoring over 12 months. This study aimed to assess how self-management affected patient preference towards future management of BP. Design and Methods: Patients with hypertension, above target clinic BP and one-or-more of stroke, diabetes, coronary heart disease or chronic kidney disease, were randomised to a self-management intervention (self-monitoring with self-titration) or usual clinic BP management. At baseline and 12 months patients were asked to rank methods of BP measurement and at 12 month follow-up were asked: "Are you planning to continue/start to self-monitor your BP after the study? Why?" Responses were coded thematically by trial arm and according to whether patients planned to continue self-monitoring. Themes were identified from the resulting codes. Scientific Data: Quantitative data regarding ranked preference for self-monitoring plus qualitative data from free text responses. Results and Conclusions: At baseline, self-monitoring was ranked as the preferred method of BP measurement by both intervention and usual care groups, but only intervention patients continued to rank self-monitoring as their preferred choice at 12 months, usual care patients preferring health professional measurement. Self-management patients were three times more likely to want to continue self-monitoring following the trial (OR 3.9 (95% CI 2.62 – 5.87; p < 0.0001). Overarching themes summarising reasons expressed by patients who wanted to continue self-monitoring included: "Positive effects of self-monitoring"; "Concern about high BP and the overall effect on health"; "Self-monitoring already part of the patients' routine/lifestyle"; and "Inspired by the study". For patients who did not want to continue/start self-monitoring, comments fell into five overarching themes: "Anxiety or concerns about self-monitoring"; "BP measured at the surgery"; "Feels BP is controlled"; "Not interested in self-monitoring"; "Never considered self-monitoring or had the opportunity to do it". Self-management provides additional features over-and-above self-monitoring including: a medication plan in advance, training patients to understand and interpret BP targets, when to increase medication and links with a health professional. These features appear to keep patients motivated to use self-monitoring as a way of managing their BP long-term and should be considered when starting patients to self-monitor.